Ablation of idiopathic ventricular arrhythmia using zero-fluoroscopy approach with equivalent efficacy and less fatigue: A multicenter comparative study. Issue 6 (February 2017) - Wang, Yan; Chen, Guang Zhi; Yao, Yan; Bai, Yang; Chu, Hui Min; Ma, Ke Zhong; Liew, Reginald; Liu, Hao; Zhong, Guo Qiang; Xue, Yu Mei; Wu, Shu Lin; Li, Yi Fu; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The efficacy of a completely zero-fluoroscopy (ZF) approach for the catheter ablation of idiopathic ventricular arrhythmias (VAs) and whether it has advantages over the conventional fluoroscopy (F) approach are still unknown. The aim of this study was to compare the safety and efficacy of a completely ZF approach with those of the conventional F approach in the ablation of idiopathic VAs. We conducted a prospective study involving 7 centers in China. Consecutive patients (n = 489, mean age 45.3 ± 15.3 years, 44.8% male) with idiopathic VAs were recruited. Eligible participants were assigned to either a ZF (n = 163) or F (n = 326) approach at a ratio of 1:2. The completely ZF approach was successful in 163 (100%) patients for electrophysiological study, and in 151 patients (94.4%) for arrhythmia ablation with 9 cases having to switch to the F approach due to the need for coronary angiography. There was no significant difference between the ZF approach and F approach in procedural success rate (84.1% vs 85.4%, respectively), arrhythmia recurrence (1.9% vs 2.2%), or severe complications (0.6% vs 0.9%). The medical staffs using the ZF approach did not wear heavy protective apparels, thus experienced significantly less fatigue compared with those using the F approach (2.1 ± 0.7 vs 3.9 ± 1.6, P  < 0.05). The completely ZF approach is as safe and efficient as the conventional F approach for the electrophysiological study and the ablation of idiopathic VAs. The medical staffs using ZF approach felt less fatigue and received less exposure to radiation.